The Narrative of the Mexican Revolution: literary period of violence - Aguilera Navarrete, Flor Esther (Acta Universitaria, 2016)
The purpose of present paper is to analyze and reflect on general delimitation of literary period of narrative of the Mexican Revolution, which began in 1915 and ended by about the mid-1940s. In addition, this objective implies to recognize violence as an important feature of this narrative period. Aforementioned reflection is going to allow to study that sociocultural moment of great political and social importance in Mexico. Albeit, from the viewpoint of a symbolic reality and under a specific ideology and literary scheme, with an undeniable flavor of truth, despite the fact that is considered a fictitious discourse. It is found in the present paper that this literary period represents, from a fictional dimension, political questions of Revolution, as well as the situation of social injustice in Mexico. Although from a peculiar perspective: the violence. As such, violence can be considered a distinctive feature not only of this literary period, but also of the historic moment of social fracture.